Strut Confinement of Simply Supports Deep Beam Using Strut Reinforcement - Eyad Sayhood; Khudayer Abdullah; Sarah Kazem (Engineering and Technology Journal, 2020)
This study investigates the effect of confining the Strut region of the deep beam by using Struts Reinforcement; which consists of four main bars enclosed by stirrups. Six specimens were tested for investigating the behavior of deep beams including; ultimate load, mid-span deflection, crack pattern, first shear and first flexure cracks, concrete surface strain and mode of failure. The specimens were tested under two symmetrical points load with and of 1 and compressive strength of 38 MPa. The main parameters were: first one the diameter of the main bars of Strut Reinforcement (8, 10, 12 mm) with constant spacing of stirrups equal to 80 while the other parameter was varied spacing of stirrups of strut reinforcement (120, 100, and 80 mm) with constant main bars diameter of 8 mm. The test results showed that the Strut confinement generally increased the ultimate load from 750 kN to 1250 kN and the ductility of the beam, confined shear cracks and strain surface across the strut and shear area and turned failures mode from shear failure to flexure. The increase in the diameter of the main bars enhanced the behavior of the beam more than the stirrups number